2003
DOI: 10.1023/a:1022513507669
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Most studies examining HIV antiretroviral medication treatment adherence involve quantitative surveys. Although these studies have identified factors associated with medical adherence, no single variable or combination of variables is sufficiently consistent to apply to any individual or group of people. Using qualitative methods, an ethnically diverse sample (N=110) of HIV+ women, men who have sex with men, and male injecting drug users in four U.S. cities were interviewed in depth to elicit their experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(44 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
“…While most studies have shown high levels of adherence to ART in resource-constrained settings Bisson et al 2008;Byakika-Tusiime et al 2005;Diabate et al 2007;Etard et al 2007;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Mills et al 2006b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;San Lio et al 2008;Tadios and Davey 2006;Weidle et al 2002;Weidle et al 2006;Weiser et al 2003) there has been little discussion about how HIV? women balance the demands of adherence to HIV ART, childcare, and antiretroviral adherence among their children who are HIV-infected.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds with research documenting that the relationship between research staff and participants mutually influenced positive attitudes toward the study (Rao, Kekwaletswe, Hosek, Martinez, & Rodriguez, 2007;Remien et al, 2003). These factors also influenced participants' altruistic feelings and the hope that a successful study would positively impact their MSM community and society at large, creating a strong commitment to building medication management skills.…”
Section: Discussionsupporting
confidence: 75%
“…While we acknowledge that challenges patients face in adhering to ART are fluid and dynamic in nature (12), this study did not demonstrate marked changes over time. However, it is important to note that while this study is one of the first to examine patient barriers longitudinally, the duration of the study interval may not have been long enough to capture the changes in barriers we would expect to see among patients currently taking ART.…”
Section: Discussionmentioning
confidence: 54%